Phylogenetic relationships of the shearwater taxa Puffinus (sensu lato) and Calonectris (Aves: Procellariiformes: Procellariidae) based on osteological characters - Salvagni, Thamara; Carlos, Caio J. (Zootaxa, 2021)
Shearwaters are among the most diverse groups of Procellariiformes, and the systematics of genera Calonectris, Ardenna and Puffinus (sensu stricto) is particularly complex. Here we present the first morphology-based phylogenetic hypothesis for the group, using 104 osteological characters (23 continuous and 81 discrete) scored for 20 extant species of shearwaters, representing 62.5% of species currently recognized. Both equal and implied weighting were used for phylogenetic analyses, and the final hypothesis presented herein is the strict consensus of the most stable trees produced by the latter. Calonectris was recovered as monophyletic (Relative Bremer Support = 75), while all other members of shearwaters were included in a single, monophyletic grouping: Puffinus (sensu lato) (RBS = 76). The monophyly of Ardenna, as suggested by all molecular-based hypotheses, was not recovered, whereas a monophyletic Puffinus (sensu stricto) is present within the larger clade. The final hypothesis, wherein shearwaters fall into the sister taxa Calonectris and Puffinus (sensu lato), is consistent with earlier classifications based on osteological evidence.